Internal Armature of the Hindgut of Pericapritermes nitobei (Shiraki) - Kanzaki, Natsumi; Ohmura, Wakako (Sociobiology, 2016)
The internal armature of the hindgut of Pericapritermes nitobei was examined under a light microscope. Termites were obtained from Iriomote Island, Okinawa Prefecture, Japan, identified based on the typological characters of soldiers and 12S (mitochondrial) ribosomal RNA sequencing, and dissected to examine hindgut morphology. The hindgut of P. nitobei could be separated into four parts, P1-P4, and P1-P3 had cuticular spines on the inner surface. P1 bore small triangular spines. P2 formed an enteric valve, composed of six finger-shaped enteric pads with triangular spines, and six marginal regions with small dot-like spines. P3 bore three different types of spines: relatively large star-shaped spines; thorn-like small spines, and long curved spines with brush-like tips.